PEMODELAN JUMLAH KASUS PNEUMONIA BALITA DI JAWA TIMUR MENGGUNAKAN REGRESI SPATIAL AUTOREGRESSIVE MOVING AVERAGE - WIDYASTUTI, MADE NARYMURTI; SRINADI, I GUSTI AYU MADE; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 8 No 3 (2019)DO - 10.24843/MTK.2019.v08.i03.p259, 2019)
The purpose of this study is to model and determine the factors that significantly influence the number of toddler pneumonia cases in East Java Province. Modeling the number of toddler pneumonia cases was conducted using spatial autoregressive moving average (SARMA) regression analysis. The results showed that the best model to modeling was SARMA (1.1) with the AIC value is  and the coefficient of determination (  is . The significant factors that affect the number of these cases are the number of toddler receiving complete basic immunization and the number of toddler receiving health services in each district/city.